Potential mapping and zoning division in the development of integrated organic areas in Kalurahan Patuk, Gunungkidul - Ratika Tulus Wahyuhana; Jeki Trimarstuti; Annisa Mu’awanah Sukmawati; Bayu Argadyanto Prabawa; Patricia Rengganis (Universitas Muhammadiyah Magelang, 2024)
This community service activity aims to map the potential of the village and establish zoning for the development of integrated organic areas in Patuk Village, Patuk Subdistrict, Gunungkidul Regency. The results obtained from this activity demonstrate that the residents of Patuk Village can comprehend the existing village potential, accompanied by mapping its various aspects. Additionally, this activity successfully enhances community knowledge and participation in determining zoning based on designated activities, facilitating the development of more targeted integrated organic areas. The mapped potential of Patuk Subdistrict includes physical and economic aspects (agriculture, plantations, animal husbandry, MSMEs). The proposed zoning for the development of integrated organic areas consists of Zone A as the center of subdistrict activities; Zone B as an organic training center; Zone C as an area for sustainable agriculture, livestock, and fisheries; and Zone D for waste processing and agricultural product processing.